Socio-economic sourcing: benefits of small business set-asides in public procurement. Issue 3 (3rd September 2018) - Hawkins, Timothy; Gravier, Michael; Randall, Wesley S.
Abstract : Purpose: Small businesses are critical to economic health and encouraged in government spending by set-asides – annual small business sourcing goals that often are not attained. Little research has explored the negative and risky stigmas associated with small business sourcing. Design/methodology/approach: This research explores reduced transaction costs of small business sourcing to government buyers. A survey of 350 government source selections reveals lower transaction costs derived from lower perceived risk of receiving a bid protest and via more efficient source selection processes. Findings: Contrary to common bias, the performance level of small businesses is no less than that of large business. Thus, small businesses engender lower transaction costs for correcting supplier's performance. On the basis of these findings, managerial and theoretical implications are discussed.